Causes of death and associated risk factors among climacteric women from Southern Brazil: a population based-study - Colpani, Verônica (BioMed Central, 2014)
BACKGROUND: Aging and menopause are particular cardiovascular risk factors for women, due to estrogen deprivation at the time of menopause. Studies show that diabetes mellitus (DM), smoking, hypertension, high body mass index (BMI), and serum lipids are associated with increased risk of cardiovascular disease (CVD), the main cause of female mortality in Brazil. The aim of this study was to assess the mortality rate, causes of death and associated risk factors in a cohort of women from Brazil. METHODS: A longitudinal population-based study of menopausal status is currently underway in a city in South Brazil. In 2010, a third follow-up of this population was performed to assess cardiovascular risk and mortality rate between 1995 and 2011. For this analysis, 358 participants were studied. At baseline, participants had completed a standardized questionnaire including demographic, lifestyle, medical and reproductive characteristics. In addition to the contacts with relatives, mortality data were obtained through review of medical records in all city hospitals and the Center for Health Information (NIS/RS-SES). Multivariate-adjusted hazard risk (HR) and 95% confidence intervals (CI95%) were estimated using Cox proportional hazards regression. Survival curves were estimated using the Kaplan-Meier curve. RESULTS: There were 17 (4.7%) deaths from all causes during the study period. Seven (41.2%) deaths were caused by CVD, including four cases of stroke and three cases of myocardial infarction. Six (35.3%) deaths were due to cancer, and four (23.5%) were due to other reasons. In the age and smoking-adjusted multivariate models, diabetes (HR 6.645, 95% CI: 1.938–22.79, p = 0.003), alcohol intake (HR 1.228, 95% CI: 1.014-1.487, p = 0.035) and postmenopausal status (HR = 6.216, 95% CI: 0.963–40.143, p = 0.055) were associated with all-cause mortality. A significant association was found between abdominal obesity (WHR ≥ 0.85) and mortality even after the adjustment for BMI (HR = 9.229, 95% IC: 2.083–41.504, p = 0.003). CONCLUSION: CVD was an important cause of mortality in this cohort and DM and/or central adiposity were associated with all-cause mortality. Lifestyle and dietary factors seem to be related to risk of mortality in middle-aged women.